2019
DOI: 10.1186/s12889-019-6752-y
|View full text |Cite
|
Sign up to set email alerts
|

Do trajectories of economic, work- and health-related disadvantages explain child welfare clients’ increased mortality risk? A prospective cohort study

Abstract: Background Past research has shown that individuals who have had experiences of out-of-home care (OHC) in childhood have increased risks of premature mortality. Prior studies also suggest that these individuals are more likely to follow long-term trajectories that are characterised by economic, work-, and health-related disadvantages, compared to majority population peers. Yet, we do not know the extent to which such trajectories may explain their elevated mortality risks. The aim of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…33 34 While the present results suggest that, instead, the impact of public care on death may be via social circumstances and potentially some indicators of health, our study sample is insufficiently mature to enable us to simultaneously run analyses in which we incorporate data on exposure, potential mediators and mortality risk. In the only study of which we are aware to have done so, indices of socioeconomic position and mental health appear to have some explanatory role in the public care–mortality relationship, 35 so providing some indirect support for the findings herein. Replication and testing using a wider range of potential mediating characteristics, such as somatic health, health behaviours, and criminality is now required.…”
Section: Discussionmentioning
confidence: 52%
“…33 34 While the present results suggest that, instead, the impact of public care on death may be via social circumstances and potentially some indicators of health, our study sample is insufficiently mature to enable us to simultaneously run analyses in which we incorporate data on exposure, potential mediators and mortality risk. In the only study of which we are aware to have done so, indices of socioeconomic position and mental health appear to have some explanatory role in the public care–mortality relationship, 35 so providing some indirect support for the findings herein. Replication and testing using a wider range of potential mediating characteristics, such as somatic health, health behaviours, and criminality is now required.…”
Section: Discussionmentioning
confidence: 52%
“…In further analyses of data from the Stockholm Birth Cohort Study -material featured in the present review 56 -socio-economic and mental health factors would appear to partially mediate the link between public care and total mortality relationship. 33 An understanding of the role of other candidate mediators including unhealthy behaviours (smoking, heavy alcohol intake, etc), given their relationships with care 20 , and trajectories of physical diseases and death, 57 is now required.…”
Section: Discussionmentioning
confidence: 99%
“…When there were multiple reports featuring the same material (e.g., Stockholm birth cohort study [32][33][34] ), the publication with the longest duration of follow-up was included on the basis that this offered the greater statistical power. Retrieved studies were identified by GDB and any potential controversial selections were resolved amongst the authors.…”
Section: Methodsmentioning
confidence: 99%
“…Children in out-of-home care (OHC) are at higher risk of adverse outcomes later in life [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This includes outcomes such as poorer mental and physical health [1,4,5,7,9,11], premature mortality [10,15,[19][20][21][22][23], less education and lower qualifications [3,4,11,13], unemployment and a more disadvantaged socioeconomic position [3,4,11,24], unstable relationships and earlier family formation [2,3,6] and poorer living conditions [4,14,18].…”
Section: Introductionmentioning
confidence: 99%